Methotrexate and interstitial lung disease: controversies and questions. A narrative review of the literature. (23rd October 2019) - Fragoulis, George E; Conway, Richard; Nikiphorou, Elena
Abstract: MTX, which is the anchor-drug for the treatment of RA, has been associated with lung injury and in particular with MTX-related pneumonitis (M-pneu). Although the frequency of M-pneu has been reported to range between 0.3 and 11.6%, more recent studies and meta-analyses have challenged that, suggesting that it is less common than previously thought. M-pneu is considered a hypersensitivity reaction usually occuring early after MTX commencement, and to be dose-independent. Furthermore, it does not seem to be truly related to the development of interstitial lung disease observed in some patients as part of the natural history of RA (RA-ILD). On the other hand, there are data suggesting that clinicians should be cautious when commencing MTX in patients with pre-existing lung disease. However, treatment should not be delayed or limited in progressive RA that could lead to RA-ILD, and MTX remains one of the central players in the treat-to-target approach. In this review, we aimed to summarize the current evidence from observational studies and clinical trials on lung disease in MTX-treated RA patients. We focus the discussion on the lack of association between M-pneu and RA-ILD.